Intraoperative radiotherapy (IORT) for breast cancer using the Intrabeam (TM) system - Kraus-Tiefenbacher, Uta; Scheda, Antonella; Steil, Volker; Hermann, Brigitte; Kehrer, Tanja; Bauer, Lelia; Melchert, Frank; Wenz, Frederik (Tumori journal, 2005)
Introduction: Intraoperative radiotherapy (IORT) with low-energy X-rays (30-50 KV) is an innovative technique that can be used both for accelerated partial breast irradiation (APBI) and intra-operative boosting in patients affected by breast cancer. Immediately after tumor resection the tumor bed can be treated with low-distance X-rays by a single high dose. Whereas often a geographic miss in covering the boost target occurs with external beam boost radiotherapy (EBRT), the purpose of IORT is to cover the tumor bed safely. This report will focus on the feasibility and technical aspects of the Intrabeam(TM) device and will summarize our experience with side effects and local control. Materials and methods: Between February 2002 and June 2003 57 breast cancer patients, all eligible for breast conserving surgery (BCS), were treated at the Mannheim Medical Center with IORT using the mobile X-ray system Intrabeam(TM). The patient population in this feasibility study was not homogeneous consisting of 49 patients with primary stage I or II breast cancer, seven with local recurrence after previous EBRT and one with a second primary in a previously irradiated breast. The selection criteria for referral for IORT included tumor size, tumor cavity size, margin status and absence of an extensive intraductal component. The previously irradiated patients with local recurrences and 16 others received IORT as single modality. In all other cases IORT was followed by EBRT with a total dose of 46 Gy in 2-Gy fractions. The intraoperatively delivered dose after tumor resection was 20 Gy prescribed to the applicator surface. EBRT was delivered with a standard two-tangential-field technique using linear accelerators with 6- or 18-MV photons. Patients were assessed every three months by their radiation oncologist or surgeon during the first year after treatment and every six months thereafter. Breast ultrasound for follow-up was done every six months and mammographies once yearly. Acute side effects were scored according to the CTC/EORTC score and late side effects according to the Lent-Soma classification. Results: Twenty-four patients received IORT only; eight patients because they had received previous radiotherapy, 16 because of a very favorable risk profile or their own preference. Thirty-three patients with tumor sizes between 1 and 30 mm and no risk factors were treated by IORT as a boost followed by EBRT. The Intrabeam(TM) system was used for IORT. The Intrabeam source produces 30-50 KV X-rays and the prescribed dose is delivered in an isotropic dose distribution around spherical applicators. Treatment time ranged between 20 and 48 minutes. No severe acute side effects or complications were observed during the first postoperative days or after 12 months. One local recurrence occurred 10 months after surgery plus IORT followed by EBRT. In two patients distant metastases were diagnosed shortly after BCS. Discussion: IORT with the Intrabeam system is a feasible method to deliver a single high radiation dose to breast cancer patients. As a preliminary boost it has the advantage of reducing the EBRT course by 1.5 weeks, and as APBI it might be a promising tool for patients with a low risk of recurrence. The treatment is well tolerated and does not cause greater damage than the expected late reaction in normal tissue.